ANALYSIS OF THE DECISION OF THE COURT OF THE RELIGION OF SLEMAN, YOGYAKARTA (NO. 796/ Pdt.G / 2018 / PA. Smn) ON THE RESCHEDULING OF MURABAHAH FINAN - Ghozali, Mohammad; Afifah, Isyna (Ijtihad : Jurnal Hukum dan Ekonomi Islam, 2019)
The increasingly diverse needs of the community place financing as the most sought after product of bankservices. And Financial Institutions are a useful institutionto help launch an economic mechanism. Islamic financialinstitutions are developing very rapidly in Indonesia. Oneof them is the Islamic People?s Financing Bank which helpsin financing. One of the most attractive products for thecommunity is the Murabaha financing contract. However,Murabaha agreements are included in the high level ofproblematic financing. This is caused by the customersgiven that they cannot be fulfilled so that they becomebroken promises. This study aims to find out the descriptionof the decision of the Sleman Religious Court No.796 /Pdt.G / 2018 / PA.Smn, knowing the rescheduling of themurabaha contract in Islam and analyzing the decisions ofthe Sleman Religious Court in handling the renewal of themurabahah agreement according to Islam. The methodused in this study is descriptive qualitative, data presentationand conclusion drawing. In collecting data, researchers usethe method of observation, interviews and documentation.The results of this study are the decisions of the SlemanReligious Court in case No.796 / Pdt.G / 2018 / PA. Smn concerning the rescheduling of murabahah contracts inaccordance with Islamic law because they have used thefoundation of Islamic law. The decision of the SlemanReligious Court only strengthened the decision to bring upa peace agreement and to schedule a murabaha agreement